1982
DOI: 10.2136/sssaj1982.03615995004600020011x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pyrophosphate, EDTA, and DTPA on Zinc Sorption by Montmorillonite

Abstract: The effects of pyrophosphate (PP), pH, ionic strength, EDTA, and DTPA on zinc (Zn) sorption by montmorillonite were studied in order to evaluate the role of pyrophosphate in Zn solubilization. In such a system PP dissolution of organic matter and its subsequent complexation of Zn was limited and would not affect the interpretation of the results. The effectiveness of PP in complexing Zn was dependent on the levels of Ca, initial PP concentration, and pH of the montmorillonite suspension. Decreased sorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…1 of soil and were recovered in the extract (Table 4), showing that added Zn was not adsorbed by the soil. The results are in agreement with those of Asher and Bar-Yosef (1982) who observed that at pH 9 Zn was not adsorbed onto a Ca-montmorillonite suspended in a 0.0096 M pyrophosphate solution containing 8.0 mg Zn dm' 3 . It can thus be concluded that Zn of the commercial chemical is not adsorbed either but only gives rise to a high background absorption.…”
Section: Soilsupporting
confidence: 93%
See 1 more Smart Citation
“…1 of soil and were recovered in the extract (Table 4), showing that added Zn was not adsorbed by the soil. The results are in agreement with those of Asher and Bar-Yosef (1982) who observed that at pH 9 Zn was not adsorbed onto a Ca-montmorillonite suspended in a 0.0096 M pyrophosphate solution containing 8.0 mg Zn dm' 3 . It can thus be concluded that Zn of the commercial chemical is not adsorbed either but only gives rise to a high background absorption.…”
Section: Soilsupporting
confidence: 93%
“…The use ofpyrophosphate solution as the extractant for Zn bound by organic matter is based on the ability of pyrophosphate to solubilize humic substances (Bremner andLees 1949, Mortvedt andOsborn 1977) and on the ability of pyrophosphate anion to form soluble complexes with Zn Bar-Yosef 1982, Bar-Yosef andAsher 1983). It has been hypothesized that polyvalent cations complexed to organic matter are responsible for keeping organic matter in a flocculated and water-insoluble state.…”
Section: H Zinc Hound By Organic Mattermentioning
confidence: 99%
“…The Na 4 P 2 O 7 extractions were performed with the procedure of Vieiriae et al (1993). The contact time was 16 h, with 0.1 M Na 4 P 2 O 7 at pH = 10: maximum efficiency is for pH N 9 (Asher and Bar-Yosef, 1982). The EDTA extraction conditions were chosen such that EDTA was in excess at equilibrium (Gesthem and Bermond, 1998).…”
Section: Measure Of Metal Concentrations and Chemical Extractionsmentioning
confidence: 99%
“…Schmitt and Sticher (1986) investigated under laboratory conditions the sorption of Cd, Cu, and Pb in soils and reported a higher availability of these heavy metals when applied concurrently due to competition for the sorption sites. Asher and Bar-Yosef (1982) measured a decrease in the sorption of Zn by Ca-rich montmorillonite with increasing concentration of KC104 in the solution. Similarly, decreases in the sorption of Pb and Cd by montmorillonite with increasing quantities of Ca-cations in solution were reported by Griffin and Au (1977), Christensen (1984), and Inskeep and Baham (1983).…”
Section: Introductionmentioning
confidence: 99%